2019
DOI: 10.1002/1878-0261.12503
|View full text |Cite
|
Sign up to set email alerts
|

HDAC7‐mediated control of tumour microenvironment maintains proliferative and stemness competence of human mammary epithelial cells

Abstract: HDAC7 is a pleiotropic transcriptional coregulator that controls different cellular fates. Here, we demonstrate that in human mammary epithelial cells, HDAC7 sustains cell proliferation and favours a population of stem‐like cells, by maintaining a proficient microenvironment. In particular, HDAC7 represses a repertoire of cytokines and other environmental factors, including elements of the insulin‐like growth factor signalling pathway, IGFBP6 and IGFBP7. This HDAC7‐regulated secretome signature predicts negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…Tar-getScan database was applied for predicting miR-489's target gene and the results showed that HDAC7 was one of the candidate target genes of miR-489. Histone deacetylase HDAC7 is proved to be involved in a variety of cellular physiological processes and as a novel target for tumor therapy [22][23][24]. Previous studies have showed that HDAC7 was involved in the malignant phenotype of glioma regulated by ZNF326 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Tar-getScan database was applied for predicting miR-489's target gene and the results showed that HDAC7 was one of the candidate target genes of miR-489. Histone deacetylase HDAC7 is proved to be involved in a variety of cellular physiological processes and as a novel target for tumor therapy [22][23][24]. Previous studies have showed that HDAC7 was involved in the malignant phenotype of glioma regulated by ZNF326 [25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that the contribution of HDACs in the regulation of inflammation response could differ from inflammatory cells to other cell types. Indeed, deletion of HDAC9 and of other class IIa HDACs in non-inflammatory cells, similarly reported the up-regulation of some inflammatory cytokines [ 26 , 75 ]. The context-dependent effects of HDAC9 could be explained by the observation that class IIa are not required to completely abolish H3K27ac.…”
Section: Hdac9 Expression In Inflammation and In The Immune Responmentioning
confidence: 99%
“…While studies are increasingly describing RIS epigenetics, detailed data about the epigenetic modifications in other types of OIS are unavailable. Additional data are desirable since increasing evidences highlight the key roles played by epigenetic regulators in maintaining OIS and counteracting oncogenic transformation [84,[111][112][113][114][115][116]. For example, in melanomas the activation of H3K9me3 demethylases (LSD1 and JMJD2C) selectively de-represses E2F target genes, allowing senescence escape and tumorigenesis [117].…”
Section: Different Types Of Ois?mentioning
confidence: 99%